YOUTH AND MORALITY IN KENYA: THE ROLE OF SCIENCE AND RELIGION - Erixon, Wamalwa Martin (IJRDO - Journal of Applied Management Science, 2016)
Morality is said to be beliefs or ideas about what is right and wrong andabout how people shout behave. It refers to a system of beliefs and valuesconcerning how people should behave, which is accepted by a particularperson or a group. In short, it be seen as a standard of behaviour. Since ithas to do with right and wrong, it is evident that any group of people orsociety would desire to follow or do what is morally right and avoid whatis morally wrong. In this context, every society would strive to inculcateand nurture what it upholds as morally good to its members. The youthare an important section of this membership as it is in them that the futureof any society and its morality abound. It thus follows that the moralityof the youths should be emphasized for a moral society tomorrow.Nonetheless, it is claimed that today there are tangible and visiblechanges in the realm of morals among the young people. There is anoutcry about the deterioration of moral values among the youth in Kenya.This poses a great challenge as regards the future. Therefore, there is anurgency to address this situation in order to rebuild the moral standard ofour youth, hence the nation of tomorrow. This paper analyzes the role ofreligion and science in addressing the problem of youth and morality inKenya. The basic assumption in this paper is that both science andreligion are unique realities in our life, and that each can contributeuniquely in combating societal problems, hence bringing about an uprightsociety. The paper further asserts that neither science nor religion cansolely address such societal problems without involving the other; theyare complimentary realities, hence the need for dialogue. The ideasadvanced in this paper will be significant and an addition to the alreadyestablished approaches to the problem of youth and morality in Kenya.The paper also poses a challenge to the conflicting relationship betweenscience and religion, hence re-thinking the approach towards one another.